2017
DOI: 10.1038/s41598-017-13549-z
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Chemical Influence of Water on the PMMA/Aluminum Oxide Hybrid Interface In Situ

Abstract: Understanding the stability of chemical interactions at the polymer/metal oxide interface under humid conditions is vital to understand the long-term durability of hybrid systems. Therefore, the interface of ultrathin PMMA films on native aluminum oxide, deposited by reactive adsorption, was studied. The characterization of the interface of the coated substrates was performed using ambient pressure X-ray photoelectron spectroscopy (APXPS), Fourier transform infrared spectroscopy in the Kretschmann geometry (AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 52 publications
4
60
0
Order By: Relevance
“…This behavior has also been observed with other polymers including a study with poly(methyl methacrylate) (PMMA) polymer, Tannebaum et al 45 found that water helps to mediate bonding. Similar observations were recently reported by Pletincx et al 46 using in-situ measurements, showing that water can stabilize the formation of carboxylate bonds on native aluminum oxides.…”
Section: Phenol-base Adhesive (Redux 775)supporting
confidence: 90%
“…This behavior has also been observed with other polymers including a study with poly(methyl methacrylate) (PMMA) polymer, Tannebaum et al 45 found that water helps to mediate bonding. Similar observations were recently reported by Pletincx et al 46 using in-situ measurements, showing that water can stabilize the formation of carboxylate bonds on native aluminum oxides.…”
Section: Phenol-base Adhesive (Redux 775)supporting
confidence: 90%
“…The typical deconvolution of PMMA C1s spectra is illustrated in Figure 2a-"plain sample" which consists of a hydrocarbon peak CC/CH at 284.57 (±0.1) eV, a beta carbon peak CCO at 285.42 (±0.16) eV, CO bond in methoxy groups at 286.47 (±0.14) eV, and a carboxyl carbon OCO peak at 288.58 (±0.2) eV. [65,66] The peak area (%) of C1s components are shown in Table 1. As seen, oxygen plasma treatment raised the carboxyl carbon peak area from 12.71% to 18.91%, which could be correlated with oxidation of PMMA and formation of carboxyl groups through plasma induced oxygen radicals.…”
Section: Resultsmentioning
confidence: 99%
“…In the nanocomposite systems, a lower number of studies using NAP-XPS can be found in the literature regarding the interaction of relevant molecules with inorganic fillers on or near the surface of the nanocomposite, e.g., the chemical state of Pt in Pt/C electrodes under humid condition [148]. Probing the interaction at organic/inorganic interfaces was recently attempted: Pletincx et al investigated the mechanism of the interactions among three components of water vapor, poly(methyl methacrylate) (PMMA) chain, and aluminum oxide surface [149]. Careful in situ examination of C(1s) and O(1s) NAP-XPS spectra suggested that water played an important role to induce hydrolysis of methyl ester group in PMMA to carboxylic acid, which is relevant for the strong adsorption of the polymer chain on the oxide surface [150].…”
Section: New Opportunity With Emerging X-ray Based Techniques Enablinmentioning
confidence: 99%